Pemanfaatan Limbah Bahan Khusus Laboratorium Pengujian Fisis untuk Pembuatan Produk Strap Tali Jam Tangan - Eko Nuraini; Fajar Lestari (UPT Laboratorium Terpadu, Universitas Diponegoro, 2022)
Crafts made from tanned leather can be of various kinds. Wallets, bags or other forms of crafts include using leather as raw materials. Likewise, many watch straps are made with various models and colors, but until now there have not been many watch strap products made from leather scraps. Practical activities at the Physical Testing Laboratory of the Yogyakarta ATK Polytechnic have produced by-products in the form of leather scraps. irregular in shape and size. So far, the Physical Testing Laboratory has not carried out the management process. So that there is a buildup that can result in the accumulation of the amount of residue. The purpose of this study is to utilize the remaining pieces of leather to make higher-value products. The benefits of research add to the contribution of the Education Laboratory Institution by increasing their creativity in managing laboratory waste into a more useful product. This research method is a qualitative descriptive, the equipment used is a sewing machine, cutting mat, cutter, scissors, ruler, silver ink, glue, manila paper and a hole punch. The process of making a watch strap begins with making a pattern, cutting, thinning, gluing, sewing and finally installing the buckle, spring bar and making holes according to the size of the buckle. Produced watch strap products made of leather scraps from the waste of practicum which have high economic value and can reduce waste pollution